(untitled) (Research, Society and Development, 2021)
Objective: To address aspects of clinical interest related to the use of silver diamine fluoride (SDF) in the management of early childhood caries (ECC) during the COVID-19 pandemic. Methods: The search for the literature review was carried out in the PubMed database. The descriptors were chosen according to their importance in delimiting the theme and the literature synthesis considered the topics: (1) clinical effectiveness, indications, and limits of SDF, and (2) clinical use of SDF in COVID-19 context. Results: COVID-19 pandemic affects all sectors of society, and especially for pediatric dentists it imposes challenges in a scenario of difficult decision-making and liable of contamination. The treatment of caries disease with SDF gains an important connotation due to its effectiveness in the arrestment and prevention of caries lesions, safety, ease use, and low cost. It is considered a minimally invasive therapy that dispenses the use of rotary instruments (which have a high potential for contamination via aerosol dispersion) and reduces complications such as pulpitis and tooth loss and, therefore, the number of appointments. Besides, SDF is an option in which there is greater behavioral acceptance by the child. As a negative point, SDF can cause aesthetic dissatisfaction due to the darkening of the affected tooth surface. Conclusion: The caries lesions control in children with ECC using SDF, during the COVID-19 pandemic, is an effective, inexpensive, and easy to apply option. In addition, it offers a lower contamination risk by the coronavirus.